2020
DOI: 10.2991/jegh.k.200908.001
|View full text |Cite
|
Sign up to set email alerts
|

Is Physical Activity Associated with Mental Health among Chinese Adolescents during Isolation in COVID-19 Pandemic?

Abstract: Background: Restricted outdoor activities and online learning during COVID-19 pandemic may pose threats on the physical and mental health of Chinese adolescents in middle schools. The study was to explore the relationship of Physical Activity (PA) and Sedentary Time (SED) with mood states among Chinese adolescents during the pandemic. Methods: A total of 4898 adolescents (16.3 ± 1.3 years old) from 49 middle schools in 13 urban and rural areas in Yan’an, China volunteered to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
92
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(123 citation statements)
references
References 50 publications
6
92
0
5
Order By: Relevance
“…Physical activity was greatly modified during the pandemic, with half of caregivers reporting decreased athletic activity in their ADHD child. Low physical activity correlated positively with depression symptoms, a result also reported in a Chinese study that showed higher physical activity was significantly related to higher positive mood in youth during the pandemic ( 37 ). A recent meta-analysis of physical activity in paediatric ADHD reported significant improvements in depression, anxiety and aggressive behaviours due to physical activity intervention, and nonsignificant improvements in hyperactive/impulsive and inattention symptoms ( 38 ).…”
Section: Discussionsupporting
confidence: 74%
“…Physical activity was greatly modified during the pandemic, with half of caregivers reporting decreased athletic activity in their ADHD child. Low physical activity correlated positively with depression symptoms, a result also reported in a Chinese study that showed higher physical activity was significantly related to higher positive mood in youth during the pandemic ( 37 ). A recent meta-analysis of physical activity in paediatric ADHD reported significant improvements in depression, anxiety and aggressive behaviours due to physical activity intervention, and nonsignificant improvements in hyperactive/impulsive and inattention symptoms ( 38 ).…”
Section: Discussionsupporting
confidence: 74%
“…They also reiterate growing concerns about physical activity in the context of pandemic-related facility closures and event cancellations. 29 , 30 , 32 They are also greatly relevant in a society characterized by both high cultural commitment to sports and high adolescent sports participation, 9 , 10 especially during the pandemic conditions, when physical activity may provide beneficial coping strategies 51 and promote resilience. 52 …”
Section: Discussionmentioning
confidence: 99%
“…All of these behaviors have been linked to an increase in mental health problems. In contrast, some studies find that boys also report higher levels of vigorous physical activity compared to girls, which may confer protection against negative mental health outcomes (Chen et al., 2020 ; Dunton et al., 2020 ; Kang et al., 2020 ; Schmidt et al., 2020 ; Wright et al., 2021 ).…”
Section: Introductionmentioning
confidence: 98%
“…In terms of explaining gender differences in mental health problems, it has been posited that pandemic control restrictions (e.g., online schooling, social distancing) impede adolescents girls' ability to rely on their social network for emotional support in stressful times (Magson et al., 2020 ). Furthermore, research has suggested that girls engage in higher levels of sedentary behavior and increased social media use/screen time and increased time sleeping compared to boys (Dunton et al., 2020 ; Ellis et al., 2020 ; Kang et al., 2020 ; Moore et al., 2020 ). All of these behaviors have been linked to an increase in mental health problems.…”
Section: Introductionmentioning
confidence: 99%